Helene Schjerfbecks Selbstbildnisse - an den Grenzen des Ich Eine hermeneutische Studie zum Porträt im 19. und 20. Jahrhundert - Landmann, Annika (Hamburg University Press, 2018)
The Finnish painter Helene Schjerfbeck (1862-1946) is one of the most famous art-ists in Finland, whereas outside the Nordic countries her works are still presented as a discovery. This thesis focuses on her self-portraits that create a core element of her oeuvre. A close reading of the self-portraits gives insight into the wide range of topics, that are inherent in the paintings and drawings. A characteristic of Schjerfbeck's imagery is a non finito aesthetic, which is more than just a matter of style. Rather, this specific aesthetic contributes to a multi-layered depiction of the self. A closer look at the historical context shows how some of her commissioned self-portraits were part of a public image of the artist, that had its origin in the first decades of the 20th century. Other works, some of them not meant for the public, give insight into a more intimate reflection, that offers visual approaches to gender, otherness, death and creativity. References to works of Tyko Sallinen, Edvard Munch, Pablo Picasso, Käthe Kollwitz or Francis Bacon help to understand Schjerfbeck's unique visual meditations on existential questions of humanity.